An extended method of estimating the fatigue performance of mechanical structures with fasteners subject to shear loads. (April 2018) - Dai, Longchao; Chen, Hang; Zhang, Yuntao; Wang, Xinwei; Feng, Xue; Bian, Yixiang; Yang, Gang
Prediction accuracy is a key problem in estimating the fatigue resistance of engineering structures. Here, we consider mechanical structures with fasteners that are simultaneously subjected to a combination of shear and tension (or compression) loads. The currently used detail fatigue rating method is modified and an extended detail fatigue rating method is proposed to improve the estimation results. This is achieved by considering the effect of the load, stress concentration, and fatigue failure criterion on the fatigue capacity. An experimental assessment is also made of many specimens with different structures. A comparison of the estimation results obtained using the extended detail fatigue rating method and the experimental results shows that the new method gives results that are acceptable in engineering practice.